Personal Selling and Digital Marketing as Key Factors in Enhancing Customer Satisfaction through Perceived Value in Automobile Purchases - Rasyifa, Fatma; Sari , Sri Nurindah (CV. HEI PUBLISHING INDONESIA, 2025)
This study examines Personal Selling and Digital Marketing as key factors that increase Customer Satisfaction through Perceived Value in automobile purchases. It uses a quantitative causal approach on data from 400 new car buyers in DKI Jakarta and West Java. Using PLS-SEM, the results confirm that both Personal Selling and Digital Marketing strongly affect Perceived Value. Perceived Value, in turn, enhances Customer Satisfaction. Digital Marketing’s effect on satisfaction is fully mediated by Perceived Value, highlighting the need for digital efforts to foster perceived benefits beyond sales. The study emphasizes integrating digital marketing data into CRM for personalized sales and smooth customer experiences bridging online and offline channels. These findings provide practical guidance for automotive marketers to improve phygital marketing strategies and customer value.